Proteomic analysis of cells in the early stages of herpes simplex virus type-1 infection reveals widespread changes in the host cell proteome. - Antrobus, R; Grant, K; Gangadharan, B; Chittenden, D; Everett, R; Zitzmann, N; Boutell, C (Wiley, 2009)
During infection by herpes simplex virus type-1 (HSV-1) the host cell undergoes widespread changes in gene expression and morphology in response to viral replication and release. However, relatively little is known about the specific proteome changes that occur during the early stages of HSV-1 replication prior to the global damaging effects of virion maturation and egress. To investigate pathways that may be activated or utilised during the early stages of HSV-1 replication, 2-DE and LC-MS/MS were used to identify cellular proteome changes at 6 h post infection. Comparative analysis of multiple gels representing whole cell extracts from mock- and HSV-1-infected HEp-2 cells revealed a total of 103 protein spot changes. Of these, 63 were up-regulated and 40 down-regulated in response to infection. Changes in selected candidate proteins were verified by Western blot analysis and their respective cellular localisations analysed by confocal microscopy. We have identified differential regulation and modification of proteins with key roles in diverse cellular pathways, including DNA replication, chromatin remodelling, mRNA stability and the ER stress response. This work represents the first global comparative analysis of HSV-1 infected cells and provides an important insight into host cell proteome changes during the early stages of HSV-1 infection.